Liver Involvement in Patients With PiZZ‐Emphysema, Candidates for Lung Transplantation. Issue 5 (24th January 2017) - Morer, L.; Choudat, L.; Dauriat, G.; Durand, F.; Cazals‐Hatem, D.; Thabut, G.; Brugière, O.; Castier, Y.; Mal, H.
Abstract : Information about the prevalence and nature of liver disorders in adults with alpha1‐antitrypsin deficiency is scarce. At our center, systematic liver biopsy screening is part of the evaluation before lung transplantation (LT) in the emphysema patients with the PiZZ phenotype. Our aim was to report our experience with this prospective screening. Clinical, liver function, and imaging parameters as well as liver histology data were analyzed for 23 consecutive adult patients with PiZZ severe emphysema referred to our center for consideration of LT from 2006 to 2014. Overall 20 (87%) featured chronic liver disease characterized by a chronic inflammation and/or a significant portal fibrosis on histology. Two of the 23 patients (8.7%) had septal fibrosis according to the Metavir and Ishak scores and met our definition of severe chronic liver disease. They were both clinically asymptomatic with normal liver function tests. On abdominal ultrasonography, the liver appeared normal in one patient and with abnormal contours in the other. Our data indicate that in adults with PiZZ‐related emphysema being evaluated for LT, most patients had some histologic involvement. The prevalence of severe liver dysfunction is <10%. Abstract : Liver biopsy on a systematic basis in adult patients with PiZZ emphysema, candidates for lung transplantation, indicates that severe liver disease defined by the Metavir and Ishak scores is present in less than 10% of patients but that most patients have some histologic involvement.